2018
DOI: 10.1016/j.exer.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids protect retinal neurons in the DBA/2J hereditary glaucoma mouse model

Abstract: The purpose of this study was to evaluate the neuroprotective effects of omega-3 polyunsaturated fatty acid (ω3-PUFA) supplementation, alone or in combination with timolol eye drops, in a mouse model of hereditary glaucoma. DBA/2J mice (8.5-month-old) were assigned to an ω3-PUFAs + timolol, ω3-PUFAs only, timolol only, or an untreated group. Treated mice received a daily gavage administration of eicosapentaenoic acid (EPA) and docosahexaenoic acid and/or topical instillation of timolol (0.5%) once a day for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 76 publications
0
23
0
1
Order By: Relevance
“…DHA, which is uniquely concentrated in retina, has been shown to have both antioxidant and anti-inflammatory properties [ 3 , 34 , 35 ]. In addition to DR, DHA deficiency has also been implicated in other diseases of the eye, including retinitis pigmentosa [ 36 ], glaucoma [ 37 , 38 ], age-related macular degeneration [ 4 ], dry eye disease [ 39 ], and Alzheimer’s related blindness [ 18 ]. A common element of all of these diseases is chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…DHA, which is uniquely concentrated in retina, has been shown to have both antioxidant and anti-inflammatory properties [ 3 , 34 , 35 ]. In addition to DR, DHA deficiency has also been implicated in other diseases of the eye, including retinitis pigmentosa [ 36 ], glaucoma [ 37 , 38 ], age-related macular degeneration [ 4 ], dry eye disease [ 39 ], and Alzheimer’s related blindness [ 18 ]. A common element of all of these diseases is chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, particular emphasis has been placed on the role of ω3 PUFAs in eye diseases. The positive effect of ω3 treatment was investigated in animal models of retinal and optic nerve pathologies45 47 48 52 and in clinical studies of AMD and dry eyes 57–59. Although the results were not conclusive, we investigated the effect of ω3 PUFAs in age-associated retinal degeneration in healthy mice.…”
Section: Discussionmentioning
confidence: 99%
“…A protective response, perhaps with a regenerative potential, was observed in ω3-treated animals, with a pronounced increase in the size of the photoreceptor outer nuclear layer (ONL) and a reduction in interleukin 18 46. Kalogerou et al demonstrated the effectiveness of ω3 PUFAs in the DBA/2J glaucoma model; retinal ganglion cells were protected against cell death and a reduced inflammatory response was observed 47…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected on Whatman (GE Healthcare, Life Sciences, Buckinghamshire, UK) filter paper and stored at À208C. Samples were processed as previously described 34,35 and once supernatants were collected and dried using an analytical evaporator, the samples were redissolved in n-hexane and analyzed using a GC flame-ionization detector (FID).…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…A protective effect, perhaps with regenerative potential, was observed in the x3-treated group, with a pronounced increase in the size of the photoreceptor outer nuclear layer (ONL) and a reduction in interleukin-18 (IL-18), a specific inflammatory marker. 34 Recently, Kalogerou et al 35 demonstrated the effectiveness of x3 in the DBA/2J glaucoma model, where retinal ganglion cells were protected against cell death. Importantly, in all of our studies, the levels of particular PUFAs, including EPA and AA, were examined during treatment, which allowed treatment dosage to be adjusted in order to achieve and maintain an AA/EPA blood ratio level~1 to 1.5.…”
mentioning
confidence: 99%